(untitled) (Eurasian Journal of Ecology, 2023)
Bovine viral diarrhea (BVD) is an acute infectious disease caused by BVD virus (BVDV). BVD is characterized by fever, lesions of the mucosal lining of the digestive tract, diarrhea, conjunctivitis and rhinitis. This disease is considered as one of the most dangerous infectious diseases in animal husbandry worldwide because of its high prevalence, persistence in the environment, and severe clinical consequences. The purpose of this study is to assess the epizootological situation on BVD of cattle, which has developed by the beginning of 2021 in various regions of the Republic of Kazakhstan. For this purpose, we retrospectively analyzed samples of cattle serum collected in 2018-2020 by ELISA for the presence of antibodies to BVDV in them. It was found that BVD in cattle was prevalent even before 2021 in a significant area of Kazakhstan, while the total seroprevalence for BVDV was 67.3% (243/361; 95% CI: 0.37-0.63). Among the animals from which serum was taken, 51.2% of the animals were vaccinated with BVDV vaccines and 48.8% of the animals were unvaccinated. The average seroprevalence of antibodies to BVDV in unvaccinated animals was 36.4% (64/176; 95% CI: 1.2-2.5) positive samples were detected in unvaccinated animals in Zerenda, Astrakhan, Tselinograd and Shortanda districts of Akmola region, also in Akzhar and Kyzylzhar districts of North Kazakhstan region and Aksu district of Almaty region. The results obtained contribute to the disclosure of the epizootological situation of BVD in the territory of Kazakhstan, which will allow the full use of effective control measures, such as total vaccination of livestock in the risky regions of the infection and the introduction of strict restrictive measures to prevent further spread of the infection to other regions of the country. Keywords: Bovine viral diarrhea, cattle, enzyme immunoassay, Pestivirus, Togaviridae.